Model of emergence evacuation route planning with contra flow and zone scheduling in disaster evacuation - Hartama, Dedy; Mawengkang, Herman; Zarlis, Muhammad; Widia Sembiring, Rahmad (Computer Science and Information Technologies, 2021)
Evacuation is characterized by rapid movement of people in unsafe locations or disaster sites to safer locations. The traffic management strategy for commonly used evacuations is the use of Shoulder-Lane, contra-flowing traffic and gradual evacuation. Contra-flow has been commonly used in traffic management by changing traffic lanes during peak hours. To implement the contra-flow operation, there are two main problems that must be decided, namely Optimal contra-flow lane configuration problem (OCLCP) and optimal contra-flow scheduling. Within the OCSP there are two approaches that can be used: zone scheduling and flow scheduling. Problem of contra-flow and zone scheduling problem is basically an Emergence evacuation route planning (EERP) issue. This research will discuss EERP with contra-flow and zone scheduling which can guarantee the movement of people in disaster area to safe area in emergency situation.